Characteristics of Pyrolysis Products of California Chaparral and Their Potential Effect on Wildland Fires - Mahsa Alizadeh; David R. Weise; Thomas H. Fletcher (Fire, 2024)
The aim of this study was to investigate the pyrolysis of selected California foliage and estimate the energy content of the released volatiles to show the significance of the pyrolysis of foliage and its role during wildland fires. While the majority of the volatiles released during the pyrolysis of foliage later combust and promote fire propagation, studies on the energy released from combustion of these compounds are scarce. Samples of chamise (Adenostoma fasciculatum), Eastwood’s manzanita (Arctostaphylos glandulosa), scrub oak (Quercus berberidifolia), hoaryleaf ceanothus (Ceanothus crassifolius), all native to southern California, and sparkleberry (Vaccinium arboreum), native to the southern U.S., were pyrolyzed at 725 °C with a heating rate of approximately 180 °C/s to mimic the conditions of wildland fires. Tar and light gases were collected and analyzed. Tar from chamise, scrub oak, ceanothus and sparkleberry was abundant in aromatics, especially phenol, while tar from manzanita was mainly composed of cycloalkenes. The four major components of light gases were CO, CO2, CH4 and H2. Estimated values for the high heating values (HHVs) of volatiles ranged between 18.9 and 23.2 (MJ/kg of biomass) with tar contributing to over 80% of the HHVs of the volatiles. Therefore, fire studies should consider the heat released from volatiles present in both tar and light gases during pyrolysis.